Adolescents Living with HIV: An Indian Profile - Sravya Kurapati; Madhu Vajpayee; Meenakshi Raina; Sreenivas Vishnubhatla (AIDS Research and Treatment)
Purpose. Although there have been studies on the presence of Human Immunodeficiency Virus (HIV) among the adult and even pediatric population, the adolescent population has been neglected. The main objective of this study was to understand and describe the profile of adolescents accessing the Integrated Counseling and Testing Centre (ICTC) at a tertiary healthcare centre in north India. This was a retrospective analysis of the data collected where, in addition to the analysis of the presence of HIV among the target population, a comparative analysis of HIV-positive and negative individuals was also carried out. Methods. Counselors at the ICTC of All India Institute of Medical Sciences recorded responses of the patients, and pre- and posttest counseling was performed appropriately. Also, HIV testing was performed using rapid tests (EIA) and ELISA. Both pre- and posttest counseling was performed for most of the patients. Also, the data collected from 2005 to May, 2011 was then retrospectively analyzed using various statistical tests, such as, Chi-square test and odds ratios. Results. Out of 979, 84 tested HIV positive. Discrimination at multiple levels was observed.The 10–14 years age group was 0.56 times more likely to be HIV positive than 15–19 year old. HIV serostatus was strongly associated with risk behavior (P=0.003) with heterosexual transmission being the most common. Conclusion. These findings highlight the profile of adolescents in India and their equation with HIV on demographic and psychosocial levels.